Pengaruh Return On Assets dan Debt To Equity Ratio terhadap Return Saham PT Mayora Indah Tbk Periode 2012-2022 - Utomo, Budi; Hendra, Dede (Universitas Pamulang, 2024)
The purpose of this study is to determine the effect of Return On Assets and Debt to Equity Ratio on Stock Return at PT Mayora Indah Tbk for the 2012-2022 period both partially and simultaneously. This type of research is associative research to determine the relationship between two or more variables. The methods used are quantitative methods by conducting descriptive statistical testing, classical assumption tests, multiple linear regression tests, correlation coefficient tests, hypothesis tests and determination coefficient tests. The results of the t test (Partial) show that Return On Assets has an insignificant effect on stock returns with a significance of 0.051 > 0.05 and a calculated t value of 2.289 < t table 2.306. The results of the partial t debt to equity ratio test have a significant effect on Stock Return with a significant value of 0.021 < 0.05 and t count 2.866 > t table 2.306. The results of Test F simultaneously return on assets and debt to equity ratio to stock return with a significant value of 0.034 < 0.05 and F value calculated 5.339 > F table 4.26. The results of the determination test showed that the variable return on assets and debt to equity ratio affected the variable stock return by 46.2%.